Поверхностные электромагнитные волны в плазмоподобной среде, граничащей со слоисто-периодической структурой - Аверков, Ю.О.; Белецкий, Н.Н.; Яковенко, В.М. (Радіофізика та електроніка, 2012)
Теоретически исследованы поверхностные электромагнитные волны на границе раздела плазмоподобной среды и слоисто-периодической структуры с элементарной ячейкой, состоящей из двух различных немагнитных диэлектриков. Изучены дисперсионные свойства поверхностных TM- и TE-электромагнитных волн в зависимости от конфигурации элементарной ячейки слоисто-периодической структуры. Показано, что взаимное расположение и толщина диэлектрических слоев в элементарной ячейке оказывает существенное влиянии на число поверхностных электромагнитных мод, особенности их спектра и условия их существования. Теоретично досліджено поверхневі електромагнітні хвилі на межі розділу плазмоподібного середовища та шарувато-періодичної структури з елементарною коміркою, яка складається з двох різних немагнітних діелектриків. Вивчено дисперсійні властивості поверхневих TM- та TE-електромагнітних хвиль залежно від конфігурації елементарної комірки шарувато-періодичної структури. Показано, що взаємне розташування і товщина діелектричних шарів в елементарній комірці суттєво впливає на число поверхневих електромагнітних мод, особливості їх спектра та умови їх існування. In this paper, we present the theoretical analysis of dispersion properties of the surface electromagnetic waves (SEMWs) of TM- and TE-types propagating at the interface between a photonic crystal and a plasma-like medium. It was assumed that an elementary cell of the photonic crystal is composed of two different non-magnetic dielectrics. The change of the trend of the SEMWs dispersion curves with the configuration of the elementary cell has been studied. We suppose that the width of the elementary cell is constant while the relationship between the widths of the dielectric layers of the elementary cell can be changed. We have shown that the layer sequence in the elementary cell and the relationship of their widths exert a significant influence on the dispersion properties of the SEMWs. It has been established that in the case where the dielectric layer with the highest dielectric constant borders on the plasma-like medium the SEMWs exist in the width frequency range at an arbitrary relationship between the layers widths. The considered structures can be used for up-to-date applications of nanoelectronics.